PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI WORD WALL DENGAN MODEL TPACK MATA PELAJARAN AKIDAH AKHLAK MATERI KISAH KETEALADANAN NABI SUALAIMAN KELAS VII MTs HIDAYATUL INSAN PALANGKA RAYA - Sahduari Sahduari; Jasiah Jasiah (CV. ADIBA AISHA AMIRA, 2025)
This research aims to develop an innovative learning medium to improve the quality of Akidah Akhlak education at MTs Hidayatul Insan Palangka Raya. The study employs the Research and Development (R&D) method with the TPACK model. The Word Wall educational game was developed through analysis, design, development and testing involving seventh-grade students. Results indicate the Word Wall game effectively enhances student motivation and learning outcomes in understanding Akidah Akhlak concepts, particularly Prophet Sualaiman's exemplary behavior. In conclusion, the Word Wall educational game with the TPACK model enhances Akidah Akhlak learning quality through innovative and interactive approaches.